1994
DOI: 10.1007/bf01447081
|View full text |Cite
|
Sign up to set email alerts
|

Particle densities and non-equilibrium in a low-pressure argon plasma jet

Abstract: Plasma diagnostic techniques have been employed to determine particle densities and temperatures in a low-pressure argon plasma jet generated by a cascade arc. These measurements allow characterization of the extent to which the plasma jet deviates from thermodynamic equilibrium and provide a basis for predicting how reactive gases will interact with the excited and ionized species in the plasma jet. It was found that the distribution of atomic states in the plasma jet is not adequately described by either loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…OES revealed that the plasma torch created by a low-temperature cascade arc consists mainly of metastable species of Ar when Ar is used as the plasma gas. 7,8 When an organic vapor is injected into the beam of Ar metastable species, the cascade arc torch (CAT) of Ar, plasma polymerization occurs. When the torch is directed at an organic polymer surface, plasma treatment of the surface occurs.…”
Section: Nature Of the Plasma Phase And The Polymerforming Reactive Smentioning
confidence: 99%
“…OES revealed that the plasma torch created by a low-temperature cascade arc consists mainly of metastable species of Ar when Ar is used as the plasma gas. 7,8 When an organic vapor is injected into the beam of Ar metastable species, the cascade arc torch (CAT) of Ar, plasma polymerization occurs. When the torch is directed at an organic polymer surface, plasma treatment of the surface occurs.…”
Section: Nature Of the Plasma Phase And The Polymerforming Reactive Smentioning
confidence: 99%
“…3,5 It can be assumed that the ratio of excited species (energy carriers) to the unexcited carrier gas is proportional to the power input given by W. This assumption can be expressed in eqs. (4) and (5), as follows.…”
Section: First Step Of Generating Plasma Of a Carrier Gasmentioning
confidence: 99%
“…Film thickness was recorded every 15-30 s during the first 5 min of a deposition and then at 1-min intervals until a constant deposition rate was obtained. A film density of 1.0 g/cm 3 was estimated from ellipsometry and thickness monitor data and did not vary by more than Ϯ0.1 g/cm 3 over the range of conditions evaluated. This estimated density was required to obtain thickness monitor data in units of Å/s and for estimating the total mass deposition rate.…”
Section: Measurement Of Deposition Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CAT polymerization process, the speed of an argon atom coming out of the cascade arc nozzle is estimated to be above the speed of sound. 10 This high-speed gas torch can be utilized to atomize liquid monomers and plasma polymerize them. The objective of this research is to reduce the internal stress of plasma polymer films by employing liquid monomers with particular molecular structure and high molecular weight for CAT polymerization.…”
Section: Introductionmentioning
confidence: 99%